Kepuasan Kerja Karyawan Dapat Ditingkatkan Melalui Kepemimpinan, Motivasi Kerja dan Lingkungan Kerja - Ika Korika Swasti; Gita Wulandari (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The purpose of this study was to explain the effect of leadership, work motivation and work environment on employee job satisfaction using the research object at PLN Icon Plus Surabaya. This research uses a quantitative approach. The population in this study were employees of PLN Icon Plus Surabaya. While the sample in this study were 64 respondents. The data analysis used in this study used the component-based Structural Equation Modeling (SEM) method using the Partial Least Square (PLS) analysis tool. the results showed that leadership was able to have a positive and significant effect on employee job satisfaction, work motivation was able to have a positive and significant effect on employee job satisfaction. and the work environment is also able to have a positive and significant effect on employee job satisfaction.